(untitled) (GEOMATE Journal, 2024)
This study investigates the effect of varying the alkali ratio and the molarity of NaOH on the compaction properties of silt stabilized with fly ash-based geopolymers. Geopolymers offer an ecologically sound alternative to traditional cementitious materials and show promise in soil stabilization applications. Fly ash is a frequently utilized precursor in producing geopolymers. Although the benefits of utilizing fly ash as a precursor for geopolymer creation and its potential for stabilizing soil have been recognized, there has been insufficient exploration into refining alkali ratios and NaOH molarities to obtain the desired compaction characteristics. This study examines the compaction characteristics of stabilized silt soil by studying the effects of alkali ratio and NaOH molarity. The standard Proctor compaction test has determined the optimum moisture content (OMC) and maximum dry density (MDD). The results indicate that the utilization of fly ash geopolymer stabilization can improve the compaction characteristics of soil by increasing its MDD and decreasing its OMC. The observed MDD reached its highest value of 16.23 kN/m3. The fly ash geopolymer stabilization MDD was reached with 14 molars of sodium hydroxide and a ratio of 2 for the alkali activator. The OMC value of 9.12% was also reached in the same conditions. The alkali ratio and NaOH molarity had a significant impact on the compaction parameters of geopolymer-stabilized silt soil. Understanding the impact of these factors is crucial for the success of soil stabilization projects.